Mobile Fixer Studio: How to repair one item at a time on campus - Gümüş Çiftçi, Hazal; Peters, Gabi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The belongings at the Arizona State University (ASU) residence halls often have a short lifespan. At the end of each year, dumpsters around campus fill up with discarded personal items, many of which are still in good condition. Despite the efforts of ASU's Zero Waste Initiative to mitigate this issue, the systematic barriers of municipal infrastructure in waste sorting and recycling significantly limit progress. In addition, students often face challenges with practical repair skills, limited resources, and perceived obsolescence. Initial research conducted by the PI of this study through campus-based repair workshops supported the concept of prioritizing repair and offered a potential change of course for personal belongings. This paper explores the conceptualization and implementation of a mobile repair station based on the university's campus through a collaborative case study on the accessibility of repair tools and education on repair techniques. The convergence of campus-based repair initiatives, with the accessibility of a mobile repair station, seeks to cultivate a culture of conscientious consumption amongst the campus community.